2023
DOI: 10.7759/cureus.34380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fat Graft Survival and Platelet-Rich Plasma Effects: The Transcriptomic Differences

Abstract: Introduction: Fat graft survival has been studied numerously but has not gone beyond hypothetical solutions. The molecular changes in survival of standard fat grafts and enhanced survival by platelet-rich plasma (PRP) are compared in this study to reveal the etiology that causes the loss of fat grafts after transplantation.Materials and methods: A New Zealand rabbit's inguinal fat pads were excised and divided into three groups: Sham, Control (C), and PRP. Each weighing 1 g, C and PRP fat were placed into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Winter et al [29] reported the statistically significant outcome of a combination therapy of PRP and fat grafting vs. two other modalities over a mean follow-up of 24 months. This synergistic effect seems to result from PRP enhancing graft survival and secretion of growth factors like vascular endothelial growth factor (VEGF) and modulating immunogenic responses, pointing to the regenerative benefits of a combined treatment [12,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Winter et al [29] reported the statistically significant outcome of a combination therapy of PRP and fat grafting vs. two other modalities over a mean follow-up of 24 months. This synergistic effect seems to result from PRP enhancing graft survival and secretion of growth factors like vascular endothelial growth factor (VEGF) and modulating immunogenic responses, pointing to the regenerative benefits of a combined treatment [12,32,33].…”
Section: Discussionmentioning
confidence: 99%